Kali Linux 2018 : Assuring Security by Penetration Testing : Unleash the full potential of Kali Linux 2018, now with updated tools, 4th Edition /: Assuring Security by Penetration Testing : Unleash the full potential of Kali Linux 2018, now with updated tools, 4th Edition. (2018) - V. N Parasram, Shiva; Samm, Alex; Boodoo, Damian; Johansen, Gerard; Allen, Lee; Heriyanto, Tedi; Ali, Shakeel
No abstract available